Post harvest handling of hot peppers (Capsicum frutescens); proceedings of a seminar - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
A Seminar on Post Harvest Handling of Hot Peppers, under the auspices of the Marketing and Agroindustry Programme of the Inter-American Institute for Cooperation in Agriculture (IICA) in collaboration with the Post Harvest Unit of the Ministry of Food Production, Marine Exploitation, Forestry and the Environment was held on the 14th December, 1988 at the Farmers' Training Center, Centeno, Trinidad and Tobago. The Seminar was designed to discuss the pre- and post-harvest handling of the hot pepper. The objective of the seminar was to train and update the participants in the most suitable pre and post harvest handling practices for hot peppers with the aim of improving the quality of the produce to become more competitive for the local as well as the export market. This document contains the edited versions of the proceedings of this seminar.